The studies on the preparation of instant noodles from wheat flour supplementing with sweet potato flour (Journal of the Bangladesh Agricultural University, 2014)
The study reports on the effect of composite flours consisting of wheat and sweet potato flour on the physicochemical and sensory properties of instant noodles. Sweet potato flour was incorporated into wheat flour at flour replacement levels of 0, 10, 20 and 30%. The levels of sweet potato flours increased in the formulations of instant noodle that increased ash, starch, crude fiber and total carbohydrate contents but decreased level of protein. The instant noodles with 20% sweet potato flour had decreased moisture content but had higher levels of fat and calories (per 100 g) when compared with 10% sweet potato flour in the formulation. The instant noodles with 0, 10, 20 and 30% of sweet potato flours that higher level of water absorption and increased volume of cooked noodles. Instant noodles with 30% sweet potato flour that the highest sensory scores for colour, flavour, texture and overall acceptability when compared with control and other samples but noodles with 20% sweet potato flour was equally acceptable. Studies on the shelf life of dried instant noodles packed in polyethylene bags showed no remarkable change in mold growth, texture and flavor but free fatty acid value, peroxide value and moisture content slightly increased gradually after 90 days duration at room temperature. DOI: http://dx.doi.org/10.3329/jbau.v12i1.21403 J. Bangladesh Agril. Univ. 12(1): 135-142, June 2014